From Green Infrastructure to Blue and Green Infrastructure Network: institutionalization of ecological connectivity at the science-policy interface. A literature review - Klervi Fustec; Alix Levain (Développement Durable et Territoires)
Nature-based solutions (NbS) is an umbrella concept that includes a variety of ecosystem-based approaches such as Green Infrastructure (GI), ecological restoration, ecosystem-based disaster risk reduction, and ecological engineering (Cohen-Shacham, 2016). Decision makers rapidly adopted the GI concept after its conceptualization was refined at the beginning of the 21st century (Wright, 2011). Environmental concepts are neither fixed nor neutral: they evolve over time and space and are intertwined within power relations (Greer and Cameron, 2015). This article draws on an in-depth social science literature review and a brief quantitative bibliometric assessment to analyze the socio-political construction of the concept, how its properties have stabilized – or not – and how it is used by stakeholders.